A Biblical Analysis of the Role of Women in Ministry Based on the Acts of the Apostles - Luther Lawing; Ratu Shandy Aulia (Edunity Kajian Ilmu Sosial dan Pendidikan, 2026)
A biblical analysis of the role of women in ministry based on the Acts of the Apostles aims to examine the role of women in ministry from a biblical perspective grounded in the Acts of the Apostles. The method used in this study is hermeneutics, employing the principles of textual and historical exegesis. This study identifies several female figures in Acts, such as Mary the mother of Jesus, Tabitha/Dorcas, Mary (the mother of John Mark), Lydia, Priscilla, and Philip’s four daughters, all of whom played important roles in the ministry of the early church. The results of the exegesis show that, although Acts was written within the context of the patriarchal Jewish culture of its time, it nevertheless records the significant contributions of women to the development of the early church. These contributions included participation in prayer ministry, social ministry, hospitality ministry, church planting, teaching, and prophetic ministry. The implications of this study affirm that women today are also called to actively participate in various forms of ministry, both within the church and in the broader community, following the biblical model demonstrated in the Acts of the Apostles.